COMPARISON OF INITIAL PARAMETERS AND FUNCTIONAL ATTRIBUTES AT DIFFERENT STAGES OF PROCESSING IN FREEZABLE AND NONFREEZABLE SEMEN - DHAKA, Y; SINGH, M; SHARMA, D K (The Indian Journal of Animal Reproduction, 2016)
Six Murrah buffalo breeding bulls with the history of donating semen of good freezability and fertility parameters, and another six Murrah bulls frequently donating either initial poor quality semen or higher degree of damage during processing were selected to study their functional parameters viz. motility, live and dead count, reaction to hypo-osmotic solution (HOS) and acrosomal integrity at four stages viz. immediately post-dilution at 37°C, post-equilibration at 4°C and at 0 h and 1 h post-thaw. In brief, it was concluded that a higher (P